1971
DOI: 10.1039/j29710000871
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic attacks on carbon–carbon double bonds. Part XIII. Vinylic substitution of 1,1-dicyano-2-p-dimethylaminophenyl-2-halogenoethylenes by aromatic amines in acetonitrile

Abstract: While the adduct (IV) may be formed by an inter-or intramolecular proton transfer t o (V), its inclusion in the reaction scheme adds very little t o the understanding of the reaction, but complicates the kinetic scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…(3) All manipulations were conducted under anaerobic and anhydrous conditions. (4) Nugent, W. A.; Harlow, R. L. J. Chem.…”
Section: References and Notesmentioning
confidence: 99%
“…(3) All manipulations were conducted under anaerobic and anhydrous conditions. (4) Nugent, W. A.; Harlow, R. L. J. Chem.…”
Section: References and Notesmentioning
confidence: 99%
“…The rate-determining step varied from the departure of the leaving group (3, to proton transfer (6,8), to the nucleophilic attack on the olefin (7). Rappoport et al (9,10) have studied the attack of primary amines on 1 , l -dicyano-2-fluoroolefins, in which the fluorine is replaced to yield a cyanoenamine. The reaction was shown to be base catalysed and a mechanism involving a competition between carbon-fluorine bond cleavage and nitrogen-hydrogen bond cleavage was proposed.…”
Section: Resultsmentioning
confidence: 99%
“…The results show that the reaction is catalysed by tertiary amines, oxalate and acetate ions, but not by alkyl ammonium ions, perchlorate or chloride ions. Rappoport and Ta-Shma (9) also found that the ammonium ion did not catalyse the reaction of p-toluidine with 1,l-dicyano-2-p-dimethylaminophenyl-2-…”
Section: Kineticsmentioning
confidence: 99%
“…Such a composite acceptor is (1,3‐dioxo‐2,3‐dihydro‐1 H ‐inden‐2‐ylidene)propanedinitrile 1 , also referred to as 2‐(dicyanomethylene‐1,3‐indanedione); CNIND may be considered to be analogous to ethenetetracarbonitrile 2 (TCNE) in its reactions. Like the latter, it readily adds N ‐nucleophiles such as secondary aliphatic and primary aromatic amines at the dicyanomethylene carbon atom with release of hydrogen cyanide, analogous to the corresponding reaction of 2 . Tertiary aromatic amines (such as N , N ‐dimethylaniline) are prone to attack with their p ‐carbon atom, followed by release of HCN .…”
Section: Introductionmentioning
confidence: 99%